Temporal evolution of acute multiple sclerosis lesions on serial sodium (23Na) MRI - Eisele, Philipp; Szabo, Kristina; Ebert, Anne; Roßmanith, Christina; Paschke, Nadia; Platten, Michael; Schönberg, Stefan; Schad, Lothar R.; Gass, Achim (Multiple Sclerosis and Related Disorders, 2019)
Background - Several studies have reported the characteristics of acute multiple sclerosis (MS) lesions on diffusion-weighted magnetic resonance imaging (DWI MRI). Current publications reported a transient reduction of the apparent diffusion coefficient (ADC) delineating an early phase of lesion evolution, before increased diffusion occurs in parallel to blood-brain-barrier (BBB) breakdown. Sodium MRI might provide another perspective on lesion development, but clinical applications have been limited to high field MR systems. The objective in this study was to investigate the temporal evolution of acute MS lesions using conventional (T2-fluid-attenuated inversion recovery (T2-FLAIR) images, post-contrast T1-weighted images), diffusion and sodium MRI. - Methods - Initial and follow-up MRI (23Na and 1H MRI) were performed on a 3T scanner. Quantitative assessment of total sodium concentration (TSC) and ADC was performed. The study was designed for frequent follow-up MRI examinations during 4 weeks after the initial presentation. - Results - Thirty-one acute MS lesions (7 lesions with reduced diffusion) in eleven MS patients were included. On initial MRI, TSC in contrast-enhancing lesions was increased when compared to the normal-appearing white matter (NAWM), while lesions with an initial reduced diffusion showed a TSC comparable to the NAWM. On follow-up MRI, in lesions with reduced diffusion subsequent increase of ADC and TSC values occurred along with signs of the development of vasogenic edema and contrast-enhancement. After four weeks, TSC values decreased along with regression of vasogenic edema and contrast-enhancement. - Conclusions - In lesions with a reduction of the ADC sodium levels are near normal and precede signs of BBB breakdown. These findings suggest a relatively preserved tissue structure in this early phase of lesion evolution.
Gesehen am 03.04.2019
Im Titel ist "23" hochgestellt